The Effect of Leadership, Working Environment and Workload on Employee Performance: The case of Human Resource Development Agency of South Sumatera Province Region (BPSDM) - Billa, Syafa Salsa; Fatimah, Fatimah; Junaidi, Junaidi (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2025)
This study aims to determine 1) The Influence of Leadership, Work Environment, and Workload on the Performance of Employees of the Regional Human Resources Development Agency of South Sumatra Province 2) The Influence of Leadership on the Performance of Employees of the Regional Human Resources Development Agency of South Sumatra Province 3) The Influence of Work Environment on the Performance of Employees of the Regional Human Resources Development Agency of South Sumatra Province 4) The Influence of Workload on the Performance of Employees of the Regional Human Resources Development Agency of South Sumatra Province. This type of research is Associative. The variables used by the researcher are leadership, work environment, workload, and employee performance. The sample in this study was 96 employees of the Regional Human Resources Development Agency of South Sumatra Province who were selected using Simple Random Sampling. The primary data used in this study was collected through a questionnaire. The data analysis technique used was Multiple Linear Regression. The results of this study indicate that (1) leadership, work environment, and workload together have a positive and significant effect on employee performance, (2) leadership has a positive and significant effect on employee performance, (3) work environment has a positive and significant effect on employee performance (4) workload has a positive and significant effect on employee performance